Customary Violations in the Walimah al-'Urs Tradition: A Study in the Perspective of Islamic Law - Mahmudin Hasibuan; Ebin Saleh Hasibuan; Alwi Hamdani Hasibuan; Maulana Ibrahim Ritonga (Islamic Circle, 2025)
This research examines customary violations in the walimah al-'urs tradition that contradict Islamic law, focusing on practices in Indonesian society. The background of the research shows that many local wedding traditions contain elements that are not in accordance with the principles of sharia, such as extravagance, discrimination, and entertainment that violate Islamic norms. The research method uses a qualitative approach through library research by analysing classical turats books such as Al-Muhazzab, Fathul Wahab, and sahih traditions from Sahih Bukhari-Muslim. Comparative analyses were conducted on the views of the four schools of fiqh as well as contemporary literature related to Islamic law and marriage traditions. The results identified three main forms of violations: entertainment practices involving gender mixing and forbidden music, discrimination in the treatment of invited guests, and extravagance that contradicts the Islamic principle of modesty. These findings are supported by qath'i propositions from the Quran and Sunnah. The discussion emphasises that Islam recognises valid customs (urf sahih) as long as they do not contradict clear texts. The study offers concrete solutions in the form of: replacing un-Islamic entertainment with halal alternatives, implementing hospitality protocols that comply with the Islamic principle of equality, and community education programmes involving religious and traditional leaders. The research conclusions present a framework for harmonising cultural traditions with sharia compliance in wedding celebrations, emphasising the supremacy of Islamic legal principles while valuing positive cultural elements. This research makes an important contribution in guiding Muslim communities to conduct sharia-compliant walimahs without losing good cultural values